The Influence of Self-Efficacy and Tolerance for Risk on the Interest in Entrepreneurship of Students of the in Medan City - Marpaung, Sasmita Angreini; Safrin, Feby Aulia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Self-Efficacy and Tolerance for Risk are important factors that influence students' excellence in business ventures. This research aims to partially and simultaneously measure the influence of SeIf-Efficacy and ToIerance for Risk on students' entrepreneurial interest in the city of Medan. This research uses a form of quantitative research with an associative approach. The research results were obtained based on several tests, namely validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests processed with IBM SPSS V.26. The results of this research are that partially and simultaneously the variables Self-Efficacy and Tolerance for Risk have a positive and significant influence on students' entrepreneurial interest in the city of Medan.